Fluorescence Detection of Cancer Stem Cell Markers Using a Sensitive Nano-Aptamer Sensor - Ding, Jie; Xu, Weiqiang; Tan, Jing; Liu, Zhifang; Huang, Guoliang; Wang, Shoushan; He, Zhiwei (Frontiers in Chemistry, 2022)
Antigen CD133 is a glycoprotein on the surface of cancer stem cell (CSC) which is a key molecule to regulate the fate of stem cells and a functional marker of stem cells. Herein, a novel fluorescence “turn-on” nano-aptamersensor for quantifying CD133 was designed using hybridization between the aptamer modified quantum dots (QDs) and gold nanoparticles (AuNPs) conjugated with partially complementary paired RNA (ssRNA). When CD133 competitively replaced ssRNA and bound to aptamer, fluorescence resonance energy transfer (FRET) would diminish between the QDs and AuNPs, which lets to an increase in fluorescent signals. The increase in fluorescence intensity was investigated to correlate linearly with the log of CD133 concentration in the range of 0-1.539 μM (R2=0.8931) and the detection limit was 6.99 nM. In confocal images, the CD133 aptamersensor was further proved to applicate in lung cancer cells sample with specificity, precision and accuracy. Compared with complicated method, this study provided a fresh approach to develop a highly sensitive and selective detection sensor for CSC in cancer tissue.